PERHITUNGAN LAJU REAKSI NEUTRON MODEL PERANGKAT ANNULAR PADA JENIS REAKTOR SCWR (SUPERCRITICAL WATER REACTOR) BAHAN BAKAR THORIUM - ismatul lisa; Yanti Yulianti; Syafriadi Syafriadi (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2018)
The calculation of fission reaction rate and capture reaction with and without filters have been done using the REACT of SRAC. The calculation of fission rate on fuel 1 and 2 were 5,39 x 10-2 reaction/cm3s with filter and 6,35 x 10-2 reaction/cm3s without filter, then of capture reaction rate with filter on fuel 1 and 2 were 2,91 x 10-2 reaction/cm3s, without filter on fuel 1 was 3,9 x 10-2reaction/cm3s and fuel 2 was 3,78 x 10-2 reaction/cm3s. The calculation of capture reaction on cladding with filter was higher than without filter was 2,15 x 10-3 reaction/cm3s, on moderator with filter was lower than without filter was 3,18 x 10-3 reaction/cm3s. The highest neutron spectrum with 1% enrichment of experiment 1 in thermal energy was 6,31 x 10-6 MeV-1 and in fast energy was 6,44 x 10-6 MeV-1, and decreased constantly. Meanwhile of experiment 2, neutron spectrum in thermal energy was 1,37 x 10-5 MeV-1 and in fast energy was 6,91 x 10-6 MeV-1, and decreased significantly from 1% to 2% enrichment then decreases constantly until 5% enrichment